Advertaising and Children: for and against - Solomonenko, Viktoria (My University, 2014)
The socialization of children into market behavior and their indoctrination into the values of consumption are vital to the continuity of a capitalist society like the United States. This article focuses on the period of childhood when new consumers are coming of age, the ways marketers shape their buying behavior, the images and values that ads associate with childhood, and the controversies and ethical questions that emerge from marketing to children. It examines these issues from the various perspectives of the advertising industry, government regulators, parents, and activists.
Keywords: advertising; marketing; children; реклама; маркетинг; діти